PERENCANAAN KEBUTUHAN BAHAN BAKU TEH MAHKOTA DEWA MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING (MRP) DI PT. SALAMA NUSANTARA KULONPROGO YOGYAKARTA - , HARYONO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In terms of natural resources, Indonesia has tremendous potential for its abundant variety of plants that have been had medical properties. One of them is mahkota dewa. According to the Central Bureau of Statistics (2012), the production of mahkota dewa has increased from the year 2009 to the year 2010 by 24.90%. It means that the mahkota dewa has potential to be developed as an industrial herbal raw material. PT. Salama Nusantara has its own mechanism in ordering supplies of raw materials every week with a pre-determined quantity. However, it turns out the company underestimated the need for raw materials carefully. The company still often has an excess or shortage of raw materials. PT. Salama Nusantara will unwittingly lead to a financial loss. Moreover, due to the fluctuating demand of teh mahkota dewa, it will also affect the availability of raw materials of the company. A good management of raw material, therefore obviously required, the Material Requirement Planning method (MRP method). This research aims to plan raw material requirement of teh mahkota dewa and to calculate inventory cost in planning raw material requirement using MRP method and comparing to the company inventory cost. Stages of the study include product demand forecasting, aggregate planning, master production scheduling, raw material planning with MRP method and inventory cost calculating. Order determine using the MRP is less than one that made by the company over the years. Based that, inventory cost based the MRP method is lower than inventory cost determine by the company. It is clear that the planning of raw material using material requirement planning method can be used as an alternative solution to save on inventory cost.